Failure of radical hysterectomy in early invasive cancer cervix: an A. H. regional cancer centre experience - Parija, Jita (International Journal of Research in Medical Sciences, 2017)
Background: Early invasive invasive carcinoma of cervix is adequately treated by surgery,radiotherapy or by combination of both.The disease-free and overall survival varies from centre to centre. Recurrence of the disease is a reflection of failure in treatment. Methods: A total of 541 cases of Radical hysterectomy with pelvic lymphadenectomy, for early stage cancer cervix performed during the period 2006 April - 2017 March at A. H. Regional Cancer Centre Cuttack, were retrospectively analysed, with an objective to identify the risk factors responsible for treatment failure. All cases were followed-up for 5 years or more. Results: Radiotherapy was supplemented in 27% of cases. Recurrence occurred in 17.18% cases. The incidence of recurrence increased from 13.9% in Stage IB to 26.3% in Stage IIB. Younger patients showed a higher recurrence of 19.16% compared to older group. Poorly differentiated squamous cell carcinoma showed 15.9% recurrence and adenocarcinoma showed 15.38% recurrence. Only 3.7% of recurrence occurred in growths <2cms which increased to 20.6% in tumors >5cms diameter. Infiltrating growths were responsible for treatment failure, recurring in 52.4%. Nodal involvement in >2 groups showed increased recurrence (30%) in contrast to 15.65% in node negative patients. Maximum recurrence occurred in the first year of treatment and beyond three years it looked safe. Adjuvant radiotherapy given in 27%, encountered 18.3% recurrence in comparison to the overall treatment failure. Conclusions: Age, stage, nature of growth, node-involvement, tumor-bulk and histo-pathological grading, combinedly altered the prognosis in early invasive cervical carcinoma treated with radical hysterectomy and selectively supplemented by radiotherapy.